pH-Responsive Polymer Nanomaterials for Tumor Therapy - Chu, Shunli; Shi, Xiaolu; Tian, Ye; Gao, Fengxiang (Frontiers in Oncology, 2022)
The complexity of the tumor microenvironment brings extreme challenges to cancer therapy while providing opportunities for targeted drug delivery. Using characteristic signals of the tumor microenvironment, various stimuli-responsive drug delivery systems can be constructed to achieve targeted drug delivery in tumor sites. Among these, pH is frequently used due to the lower pH in the tumor microenvironment. pH-responsive polymer-carriers can improve the efficiency of drug delivery in vivo, allow targeted drug delivery, reduce adverse drug reactions, and easier to achieve multifunctional and personalized treatment. pH-responsive polymers have gained increasing interest due to their potential applications and remarkable properties advantages for tumor therapy. In this review, recent advances and the common applications of pH-responsive polymer nanomaterials for drug delivery in cancer therapy are summarized, with a focus on discussing the different types of pH-responsive polymers. Moreover, the challenges and future applications have prospected.